Plain Tote Bag into a Work of Art: Tie-Dye Workshop at Bayongbong Elementary School, Serang Regency, Banten - Heru Budi Kusuma; Luisa Octania Sutanto; Melissa Thanos (Journal of Innovation and Community Engagement, 2025)
The main objective of the training is to provide a fun and educational learning experience, while introducing basic tote bag coloring techniques and developing creativity. First and second-grade students are generally unfamiliar with art techniques like tie-dye, which require creative exploration of color and shape. The activity is conducted in groups to encourage collaboration. Students are invited to create simple tie-dye creations using white tote bags, rubber bands, and safe textile dyes. The implementation process begins with a brief introduction to tie-dye and examples of its work to arouse students' interest. Next, students are introduced to the tools and materials needed, namely plain tote bags, textile dyes, and rubber bands. The next step is a demonstration of tote bag tying and coloring techniques. The PKM Team and Teachers, as facilitators, demonstrate several basic techniques slowly and provide guidance to ensure that each student understands how. It is important to give students the freedom to try the tying techniques they want, encouraging exploration and experimentation. Training evaluation is not only seen from the results of the work, but also from the process of students in creating, independence, and collaboration between friends. Effective implementation requires careful planning, availability of materials, and patient and supportive guidance, ensuring that every SDN Bayongbong student can participate and enjoy this creative process. Tie-dye training is very beneficial for children because it trains fine motor skills and hand coordination when tying tote bags, pouring colors, and folding tote bags.